(3GdCMcGe GdTQYjI GdcHQis - (3YHO GdMb Hf YHO GdQMef Hf YHO Gddg GdCROj GdETHjdj, CHh eMeO, GdeYQha H` GHf GdNQGW,J (B581 (3g` s
(3ChdgG (B:s
(3cJGH GdUdGI bSe Yf WGQb Hf Yf YHO Gddg Hf jMji CHh eMeO Cf GdhJQ hGLH abGd YHGOI Hf GdUGeJ cPH CHh eMeO CTgO Cfi SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd NeS UdhGJ GaJQVgf Gddg YR hLd s
(3BNQgG (B:s
(3Cf QShd Gddg Udi Gddg Ydjg hSde bGd ef bYO ai eUdGI Mjf jfUQa ef GdUHM MJi jSHM QcYJjf GdVMi dGjbhd GdCNjQkG ZaQdg NWGjGg hEf cGfJ CcKQ ef RHO GdHMQ ced GdSaQ GdKGfi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B281 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B92s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdedcjI HeOjfI GdQHGW (B(1/ 5380) s
Keywords: (3Gdabg GdeGdcjs